Correlation between serum vitamin levels and gestational diabetes mellitus - Qin, Ying; Song, Qinwen; Jiang, Xiaoyuan; Su, Yixin; Chen, Hua; Ji, Xiao; Xu, Shujing (Frontiers in Endocrinology, 2025)
Gestational diabetes mellitus (GDM) is a common clinical complication during pregnancy, with its pathogenesis not yet fully elucidated. Vitamin D contributes to GDM pathogenesis by regulating pancreatic β-cell function, immune responses, and lipid metabolism. Vitamin D deficiency may contribute to GDM through these mechanisms. Vitamin E levels in GDM patients are lower than those in normal pregnant women, and its deficiency may increase the risk of GDM, potentially due to its antioxidant properties, although the specific mechanisms remain unclear. The relationship between vitamin A levels and GDM is controversial. Additionally, the occurrence of GDM is closely associated with one-carbon metabolism, involving folic acid (vitamin B9), vitamin B12, and vitamin B6. Deficiencies in these vitamins may lead to homocysteine metabolism disorders, thereby contributing to GDM. Vitamin B3 plays a protective role against GDM by regulating redox reactions. Vitamin C deficiency has also been linked to GDM. Furthermore, combined supplementation with vitamin C and iron has been shown to reduce the incidence of pregnancy-associated iron-deficiency anemia to some extent.